Bells of Coronado - Witney, William, 1915-2002; Nibley, Sloan; Rogers, Roy, 1911-1998; Rogers, Dale Evans; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures, 1950)
Posing as a cowhand, Roy searches for a mysterious murderer plotting to sell stolen uranium to an unfriendly power.
Originally released as a motion picture in 1950.
Roy Rogers, Trigger, Dale Evasn, Pat Brady, Grant Withers, Foy Willing and the Riders of the Purple Sage.
Cinematographer, John MacBurnie; editor, Tony Martinelli; music, Dale Butts.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Conspiracies -- Drama; Murderers -- Drama; Treason -- Drama; Western films; Musical films; Feature films; Internet videos; Streaming video